Taxation of crypto assets - Schmidt, Niklas; Bernstein, Jack; Richter, Stefan; Zarlenga, Lisa M. (Kluwer Kluwer, 2021)
Taxation of Crypto Assets' begins with an overview of the technology and characteristics of crypto assets as well as the key tax concepts and types of taxes that could apply to them. The emergence of crypto assets has required taxation authorities worldwide to develop unprecedented policies and compelled tax lawyers to apply existing laws in new ways. One of its kind, this book provides a detailed country-by-country analysis of how the tax law of thirty-nine countries may apply to this rapidly developing area, including different use cases and compliance and documentation requirements.